Peranan Methylobacterium spp. dalam Meningkatkan dan Mempertahankan Vigor Benih Kedelai - Ratri Tri Hapsari; Selly Salma; Eni Widajati; Maryati Sari (Iptek Tanaman Pangan, 2016)
Soybean is considered as a functional food, due to its status as source of protein in Indonesia dietary. The soybean seeds determine the quality of soybean products through a better crop in the farm. Factor limiting the supply of soybean seeds in the tropics is the rapid deterioration of seed germination during storage, thereby reduces the availability of high quality of seed. Seed vigor is divided into two categories, namely the seed growth strength vigor and longevity seed vigor. Seed growth strength vigor indicates the growing strength in a suboptimum condition, while seed longevity vigor is the ability of seed lot to be stored in a suboptimum condition. Seed treatment uses beneficial microbes can protect plants in the nursery stage, and during the plant life cycle. Methylobacterium spp can live in a single-carbon compounds of the plant, such as metanol (CH3OH) or methylamine (CH3NH2) as a carbon source. Methylobacterium spp can produce IAA, GA3 and transzeatin. Methylobacterium spp can produce PQQ and tocopherol, one of the antioxidants that limit the nonenzimatic lipid oxidation during seed storage, germination and early seedling development. Methylobacterium spp can be used to improve the germination of soybean seed through seed inoculation, while maintaining soybean seed longevity can be obtained by coating the seed with Methylobacterium spp.